Exceptions to the Right to Be Forgotten in Relation to Press Freedom in the Digital Era - Theon Charles; Kiki Kristanto; Rizki Setyowibowo Sangalang (Dinasti Research, 2025)
The rapid development of technology has significantly transformed the dissemination and accessibility of information in Indonesia. With 77% of the population being internet users in 2023, issues surrounding personal data protection and freedom of the press are becoming increasingly critical. The